Peptide nanovesicles: supramolecular assembly of branched amphiphilic peptides - Gudlur, Sushanth (Kansas State University, 2012)
Peptide-based delivery systems show great potential as safer drug delivery vehicles. They overcome problems associated with lipid-based or viral delivery systems, vis-a-vis stability, specificity, inflammation, antigenicity, and tune-ability. We have designed and synthesized a set of 15 and 23-residue branched, amphiphilic peptides that mimic phosphoglycerides in molecular architecture. They undergo supramolecular self-assembly and form solvent-filled, bilayer delineated spheres with 50-150 nm diameters (confirmed by TEM and DLS). Whereas weak hydrophobic forces drive and sustain lipid bilayer assemblies, these structures are further stabilized by β-sheet hydrogen bonding and are stable at very low concentrations and even in the presence of SDS, urea and trypsin as confirmed by circular dichroism spectroscopy. Given sufficient time, they fuse together to form larger assemblies and trap compounds of different sizes within the enclosed space. They are prepared using a protocol that is similar to preparing lipid vesicles. We have shown that different concentrations of the fluorescent dye, 5(6)-Carboxyfluorescein can be encapsulated in these assemblies and delivered into human lens epithelial cells and MCF-7 cells grown on coverslips. Besides fluorescent dyes, we have delivered the plasmid (EGFP-N3, 4.7kb) into N/N 1003A lens epithelial cells and observed expression of EGFP (in the presence and absence of a selection media). In the case of large molecules like DNA, these assemblies act as nanoparticles and offer some protection to DNA against certain nucleases. Linear peptides that lacked a branching point and other branched peptides with their sequences randomized did not show any of the lipid-like properties exhibited by the branched peptides. The peptides can be chemically decorated with target specific sequences for use as DDS for targeted delivery.
Keywords: Peptide nanovesicles; Branched peptides; Amphiphilic peptides; Peptide vesicles; Biochemistry (0487)